MAIT Cells Display a Specific Response to Type 1 IFN Underlying the Adjuvant Effect of TLR7/8 Ligands - Pavlovic, Marion; Gross, Christelle; Chili, Chahinaize; Secher, Thomas; Treiner, Emmanuel (Frontiers in Immunology, 2020)
Mucosal-Associated Invariant T (MAIT) cells constitute a highly conserved subset of effector T cells with innate-like recognition of a wide array of bacteria and fungi in humans. Harnessing the potential of these cells could represent a major advance as a new immunotherapy approach to fight difficult-to-treat bacterial infections. However, despite recent advances in the design of potent agonistic ligands for MAIT cells, it has become increasingly evident that adjuvants are required to elicit potent anti-microbial effector functions by these cells, such as IFNalpha production and cytotoxicity. Indeed, TCR triggering alone elicits mostly barrier repair functions in MAIT cells, whereas an inflammatory milieu is required to drive the anti-bacterial functions. Cytokines such as IL-7, IL-12 and IL-18, IL-15 or more recently type 1 IFN all display an apparently similar ability to synergize with TCR stimulation to induce IFNalpha production and/or cytotoxic functions in vitro, but their mechanisms of action are not well established. Herein, we show that MAIT cells feature a build-in mechanism to respond to IFNalpha. We confirm that IFNalpha acts directly and specifically on MAIT cells, and synergizes with TCR/CD3 triggering to induce maximum cytokine production and cytotoxic functions. We provide evidences suggesting that the preferential activation of the Stat4 pathway is involved in the high sensitivity of MAIT cells to IFNalpha stimulation. Finally, gene expression data confirm the specific responsiveness of MAIT cells to IFNalpha and pinpoints specific pathways that could be the target of this cytokine. Altogether, these data highlight the potential of IFNalpha-inducing adjuvants to maximize MAIT cells responsiveness to purified ligands in order to induce potent anti-infectious responses.